SPEED CONTROL OF PNEUMATIC CYLINDERS USING HIGH SPEED 2 PORT ON/OFF VALVES WITH PULSE WIDTH MODULATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This paper presents the possibility of controlling the speed of a different types of pneumatic cylinder with high speed 2-position valves a controller using Pulse Width Modulation /PWM/. To increase the energy efficiency of pneumatic power transmission systems, modern control method for speed control pneumatic cylinders is applied. This is realised by high speed 2 port ON/OFF valves, digital control by computer and virtual instruments made with specialized software. An electronic block implemented with a PWM and an energy saving amplifier is used for control high speed 2 port ON/OFF valves. Practical realization of PWM controlled electropneumatic power transmission system is shown and experimental characteristics for variable speed of the pneumatic actuator are obtained. The experimental results are shown in few graphs. The presented experimental studies prove the possibility of smoothly adjusting the speed of pneumatic cylinders using two-position valves, controlled with PWM. Using this control method makes it possible to replace expensive servo valves for precise speed control.